2012
DOI: 10.1152/ajpheart.00470.2011
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal displacement and intramural shear strain of the porcine carotid artery undergo profound changes in response to catecholamines

Abstract: Ahlgren ÅR, Cinthio M, Steen S, Nilsson T, Sjöberg T, Persson HW, Lindström K. Longitudinal displacement and intramural shear strain of the porcine carotid artery undergo profound changes in response to catecholamines. Am J Physiol Heart Circ Physiol 302: H1102-H1115, 2012. First published December 23, 2011 doi:10.1152/ajpheart.00470.2011The effects of catecholamines on longitudinal displacements and intramural shear strain of the arterial wall are unexplored. Therefore, the common carotid artery of five anae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
51
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 31 publications
7
51
0
Order By: Relevance
“…2). The administration of an alternative drug to induce hypertension may have induced larger longitudinal strains than Phenylephrine, since arterial longitudinal motion has showed to increase in response to catecholamines [16]. However, the inner-most layer of the artery wall showed to increase more in longitudinal motion than the adventitia, resulting in an increased longitudinal shear strain.…”
Section: Discussionmentioning
confidence: 99%
“…2). The administration of an alternative drug to induce hypertension may have induced larger longitudinal strains than Phenylephrine, since arterial longitudinal motion has showed to increase in response to catecholamines [16]. However, the inner-most layer of the artery wall showed to increase more in longitudinal motion than the adventitia, resulting in an increased longitudinal shear strain.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that the outer part of the arterial wall, the adventitial region, in these arteries exhibit the same basic pattern of longitudinal movement, but the magnitude of movement is smaller than that of the intima-media complex, thereby indicating the presence of previously unknown substantial shear strain and, thus, shear stress intramurally (Cinthio et al 2006). In addition, we found that the major circulating hormones that play a role in vascular tone, adrenaline and noradrenaline, can dramatically increase longitudinal movement ), suggesting that the longitudinal movement can be a missing link between mental stress and cardiovascular disease (Ahlgren et al 2012b). It has been hypothesized that the pattern and/or magnitude of longitudinal arterial wall movement can be used as a biomarker for cardiovascular disease (Ahlgren et al , 2012a(Ahlgren et al , 2012bCinthio et al 2006;Svedlund and Gan 2011a;Svedlund et al 2011;Zahnd et al 2011Zahnd et al , 2012a.…”
Section: Introductionmentioning
confidence: 91%
“…The intima-media of these arteries exhibits a longitudinal displacement that is larger than that of the adventitial region [18] and thus, there is shear strain and shear stress within the arterial wall [18][19][20][21]. We have recently reported that longitudinal movement and intramural shear strain undergo profound changes in response to the important circulatory hormones adrenalin and noradrenalin [22], indicating that the longitudinal movements and resulting intramural shear strain can constitute an important but overlooked mechanism in the cardiovascular system. Studies have indicated that the maximal amplitude of the longitudinal displacement of the common carotid artery is reduced in subjects with cardiovascular risk factors [23], and suspected and manifest atherosclerotic disease [24,25].…”
Section: Introductionmentioning
confidence: 99%